Relation of Hypocholesterolemia With Diabetes Mellitus in Patients With Coronary Artery Disease - Ndrepepa, Gjin; Cassese, Salvatore; Xhepa, Erion; Fusaro, Massimiliano; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Kastrati, Adnan (American Journal of Cardiology, 2020)
The association between hypocholesterolemia and diabetes mellitus (DM) in patients with coronary artery disease (CAD) remains poorly investigated. We undertook this study to investigate whether there is an association between hypocholesterolemia and odds of DM in these patients. This observational study included 14,952 patients with CAD: 8,592 without statins (statin-naive group) and 6,360 with statins on admission (statin-treated group). Hypocholesterolemia was defined as a total cholesterol within the first quintile of the total cholesterol concentration (total cholesterol <157 mg/dl). The primary outcome measure of this study was presence of DM. Hypocholesterolemia was present in 2,926 patients (20%; 1,102 statin-naive patients and 1,824 statin-treated patients). DM was present in 1,029 patients with hypocholesterolemia and 2,793 patients without hypocholesterolemia (35% vs 23%; odds ratio [OR] 1.79, 95% confidence interval [CI] 1.64 to 1.96; p <0.001). After adjustment, hypocholesterolemia was independently associated with the odds of DM in all patients (adjusted OR 1.55 [1.38 to 1.74]; p <0.001), statin-naive patients (adjusted OR 1.51 [1.25 to 1.82]; p <0.001) and statin-treated patients (adjusted OR 1.64 [1.41 to 1.91]; p <0.001). For every 20 mg/dl lower total cholesterol, the odds of being with DM increased by 14% (adjusted OR 1.14 [1.11 to 1.16]; p <0.001) with no cholesterol-by-statin interaction (Pint = 0.803). The association between hypocholesterolemia and odds of DM was entirely driven by low-density lipoprotein-cholesterol. For every 20 mg/dl lower low-density lipoprotein-cholesterol, the odds of DM increased by 14 % (adjusted OR 1.14 [1.11 to 1.16]; p <0.001). In conclusion, in patients with CAD, hypocholesterolemia was independently associated with the odds of DM with a dose-response relation and no cholesterol-by-statin interaction.
CRIS-Team Scopus Importer:2023-03-08